The Agrarian Receipts as an Instrument of Financial-Credit Support for Small and Medium-Sized Agricultural Producers - Abramova Iryna V. (Bìznes Inform, 2018)
The article is aimed at a theoretical substantiation and development of practical recommendations on the financial-credit support for small and medium-sized agricultural producers using agrarian receipts. It is determined that Ukrainian farmers are in permanent search for sources of financing of own business. Nowadays bank lending is the most popular among farmers. It has been proved that the system of financing under the pledge of the future harvest with use of agrarian receipts can become an effective instrument of attraction of credit resources by small and average agricultural producers. The comparative analysis of bank lending and crediting using agrarian receipts have showed that the latter are more adapted to the needs of agricultural producers, because of taking into account the seasonal nature of agricultural production, also they are a fairly transparent tool. In case of non-fulfillment of obligations on agrarian receipts, the legislation provides a simple and clear procedure of collection without court proceedings. Despite the obvious advantages of agrarian receipts, the process of their spread in the agrarian sector of the country’s economy is hampered by low awareness of agricultural producers with the mechanism of their use, lack of proper registration of lands in some farmers, insufficient work-out of issues related to repayment of loans, and other problems.